Predictive Accuracy of Wideband Absorbance under Various Pressure Conditions in Identifying Infants with a Conductive Hearing Loss. - Aithal, Sreedevi; Aithal, Venkatesh; Kei, Joseph; Wilson, Matthew (Journal of the American Academy of Audiology, 2024)
Objective The objectives of the study were to (i) evaluate the effectiveness of wideband absorbance (WBA) at ambient pressure (WBA amb), tympanic peak pressure (WBA TPP), and 0 daPa (WBA 0) to identify conductive hearing loss (CHL) in infants and (ii) compare the sensitivity and specificity of the three WBA tests with that of high-frequency tympanometry (HFT) and transient-evoked otoacoustic emissions (TEOAE). Method A total of 31 ears with hearing thresholds no greater than 20 dB HL (reference group from 20 infants [mean age: 3.1 weeks]) and 47 ears with CHL from 31 infants (mean age: 3.4 weeks) were included in the study. Hearing threshold was determined using air-conduction tone-burst auditory brainstem response (TB-ABR) test, whereas CHL was determined using both air- and bone-conduction TB-ABR tests. HFT with a 1000-Hz probe tone, TEOAE, and WBA tests were conducted on all participants. Results WBA amb, WBA TPP , and WBA 0 of the CHL group were significantly lower than that of the reference group across a wide frequency range. Area under the receiver operating characteristic (AROC) curve for detecting CHL varied from 0.51 to 0.9 depending on the frequency. The highest AROC was obtained at 1.25 kHz for WBA amb (0.79), at 1.5 kHz for WBA TPP (0.9) and at 1 kHz for WBA 0 (0.80). The sensitivity and specificity were 0.98 and 0.45, respectively for HFT, and 1.0 and 0.6, respectively for TEOAE. In comparison, the WBA test had slightly lower sensitivity but higher specificity than the HFT and TEOAE tests. Conclusion WBA TPP at 1.5 kHz can identify CHL in infants as good as, if not more accurately than, WBA amb or WBA 0. WBA TPP test had good balance of high sensitivity and specificity compared with HFT and TEOAE. The three WBA tests are useful tools for identifying CHL in infants under 6 weeks of age.